Adherence to treatment in allergic rhinitis using mobile technology. the mask study - Menditto,E; Costa,E; Midão,L; Bosnic-Anticevich,S; Novellino,E; Bialek,S; Briedis,V; Mair,A; Rajabian-Soderlund,R; Arnavielhe,S; Bedbrook,A; Czarlewski,W; et al. (Clinical and Experimental Allergy, 2019)
BACKGROUND: Mobile technology may help to better understand the adherence to treatment MASK-rhinitis (Mobile Airways Sentinel NetworK for allergic rhinitis) is a patient-centered ICT system. A mobile phone app (the Allergy Diary) central to MASK is available in 22 countries. OBJECTIVES: To assess the adherence to treatment in allergic rhinitis patients using the Allergy Diary App. METHODS: An observational cross-sectional study was carried out on all users who filled in the Allergy Diary from January 1, 2016 to August 1, 2017. Secondary adherence was assessed by using the modified Medication Possession Ratio (MPR) and the Proportion of days covered (PDC) approach. RESULTS: 12,143 users were registered. 6,949 users reported at least one VAS data recording. Among them, 1,887 users reported ≥ 7 VAS data. 1,195 subjects were included in the analysis of adherence. 136 (11.28%) users were adherent (MPR ≥70% and PDC ≤ 1.25), 51 (4.23%) were partly adherent (MPR ≥70% and PDC =1.50) and 176 (14.60%) were switchers. On the other hand, 832 (69.05%) users were non-adherent to medications (MPR<70%). Of those, the largest group was non-adherent to medications and the time interval was increased in 442 (36.68%) users. CONCLUSION AND CLINICAL RELEVANCE: Adherence to treatment is low. The relative efficacy of continuous versus on-demand treatment for AR symptoms is still a matter of debate.This study shows an approach for measuring retrospective adherence based on a mobile app. This represent a novel approach also for analyzing medication taking behavior in a real-world setting. This article is protected by copyright. All rights reserved.